Study on the High Precision Manufacturing of the Hourglass Worm Drive Pair in the Solar Tracking System - Chen Yan; Gong Yuxia (Jixie chuandong)
At present,the problems of the poor accuracy and low efficiency etc exist in the solar tracking system,one of the main reasons is that the hourglass worm drive pair is not the right conjugating transmission form. Aiming at the wrong transmission form of the hourglass worm drive in the solar tracking system,based on the differential geometry and the space meshing theory,the accurately mathematical model of involute enveloping hourglass worm is deduced. The precise 3D model of the hourglass worm tooth surface is established,and the contact areas are shown based on the graphics. The involute enveloping hourglass worm is manufactured in the DMG turning and milling machining center,and the contact pattern comparison test is carried out. The results show that the mathematical model and the 3D model are correct,as well as the manufacture method is feasible.